PENERAPAN KUALITAS PELAYANAN,PENERBITAN SURAT TAGIHAN PAJAK TERHADAP PENDAPATAN PAJAK KENDARAAN BERMOTOR (PKB) - Jennah, Roihatul; Fanani Rohma, Frida (Lembaga Penelitian, Publikasi dan Pengabdian Pada Masyarakat, 2024)
This type of research is descriptive research with a qualitative approach. The informants in this research were motor vehicle tax payers. The data obtained from the Bapenda UPT Bangkalan office which manages motor vehicle taxation (PKB), with direct services by the Bangkalan Samsat, and of course regarding whether services can be an obstacle or smoothness to tax revenues. to find out regarding the issuance of tax bills, where there are 3 follow-up SPSOs (letter collecting data on motor vehicle tax subjects and objects), late payment of PKB within 14 days. NPP (motor vehicle tax calculation note), late payment of PKB within 1 month. NTP (motor vehicle tax bill note), Late payment of PKB within 2 months. On motor vehicle tax revenue. The data used in this research is data obtained directly from Samsat. From the results of the analysis above, whether implementing service quality and issuing tax bills (STP) is beneficial for the level of tax revenue.